Settlement behavior of shallow foundations in unsaturated soils under rainfall - Kim, Yongmin (2018)
Shallow foundations are often situated on unsaturated zones above the groundwater table. In this study, the influence of rainfall infiltration on the settlement behavior of shallow foundations was investigated using numerical analyses. The numerical solutions were compared with experimental data from in-situ load tests. The relative importance of rainfall intensities and groundwater table positions in inducing the additional settlement of shallow foundations was examined through a series of parametric studies. Two different groundwater table positions contributing to settlements and three assorted rainfall intensities were used in the numerical analyses. Typical soil properties of two main residual soils in Korea were incorporated into the numerical analyses. Special attention is given to the sequential analysis procedure comprised of a flow analysis and deformation analysis. Load-settlement relationships obtained from the numerical methodology in the present study were in good agreement with the field measurements. Results from the parametric studies showed that the rainfall intensity plays a significant role in the settlement behavior of shallow foundations in unsaturated soils. The changes in the settlement during rainfall were also affected by the groundwater table position near the ground surface due to changes in matric suction. In addition, higher bearing capacity in response to rainfall infiltration was observed in the soil with smaller permeability function as compared to larger permeability function.